Properties of callers who called a telephone information hot line for problems related with alcohol and other drugs and efficiency of the line - Türkcan, Ahmet; Yazman, Ümit; Özgür, Selda; Korkut, Asuman; Ertan, Nurten; Çakmak, Duran (Journal of Dependence, 2001)
Object: This study is designed to determine the sociodemographic properties of people who called the AMATEM Substance Abuse Information Hot Line in 1999.Their reasons to call and the productivity of the line is also evaluated.Method: Information about the people who called the line in 1999 was collected through 15 item questionnaire. Obtained data was evaluated by SPSS.Results: 3303 people called the line in 1999 and the information gathered is as follow: 31.2% of the callerswere using any substance and 61.8 % declared him/herself as a relative or a friend. 65.7% of callers asked information about alcohol while 17% cannabis, 15% heroin, 10% pharmaceutical medicine, 7.5% volatiles, 6.5% cigarettes, 5.6% cocaine and 13.8% asked information on more than one substance. 76.6% of the callers who were using any substance, declared that they have never been in treatment before.Conclusion: Majority of the people who called this line were the relatives of substance users. This shows that those people are in need of information. It is remarkable that vast majority of drug abusers who called the line has never been in treatment before and information hot line has an impact on developing the treatment motivation and its effectiveness.
Keywords: Alcohol; drug; telephone